2010
DOI: 10.1016/s1470-2045(10)70038-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thromboembolic diseases in men with prostate cancer: results from the population-based PCBaSe Sweden

Abstract: SummaryBackgroundCancer is associated with an increased risk of thromboembolic diseases, but data on the association between prostate cancer and thromboembolic diseases are scarce. We investigated the risk of thromboembolic disease in men with prostate cancer who were receiving endocrine treatment, curative treatment, or surveillance.MethodsWe analysed data from PCBaSe Sweden, a database based on the National Prostate Cancer Register, which covers over 96% of prostate cancer cases in Sweden. Standardised incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 35 publications
10
92
0
3
Order By: Relevance
“…Evidence from other studies suggests an increased risk of TED in men with PCa who undergo radical prostatectomy (RP) and pelvic lymph node dissection (PLND) [3,5]. We also found the risk of TED to be greater in all men with PCa and this risk was highest among men who underwent ADT, with a twofold increased risk of PE in these individuals vs the general Swedish male population [2]. This indicates that ADT alone may play a significant role in the increased risk of TED [2,3,5].…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Evidence from other studies suggests an increased risk of TED in men with PCa who undergo radical prostatectomy (RP) and pelvic lymph node dissection (PLND) [3,5]. We also found the risk of TED to be greater in all men with PCa and this risk was highest among men who underwent ADT, with a twofold increased risk of PE in these individuals vs the general Swedish male population [2]. This indicates that ADT alone may play a significant role in the increased risk of TED [2,3,5].…”
Section: Introductionsupporting
confidence: 66%
“…Previous analyses from the Prostate Cancer Database (PCBaSe) Sweden have shown that men on ADT are at the highest risk of TED among all men with PCa and that surgeries for PCa are associated with an increased risk of TED [1,2]. When comparing 45 065 men with PCa who underwent cancer surgery with an age-and residency-matched control population, we found a threefold increase in risk of pulmonary embolism (PE) after TURP [1].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Infarction results when the tumor fragment is large enough to occlude the tissue's arterial perfusion. Most tumor emboli occur during surgery; a few occur in the early postoperative period (8)(9)(10)(11)(12). The delayed occurrence of these emboli may be due to tumor fragments that remain loosely adhered to the site of pulmonary vein ligation and then embolize after surgery with coughing or other movement, or perhaps emboli are temporarily detained in the left ventricular trabeculations or chordae tendineae (1,2).…”
Section: Discussionmentioning
confidence: 99%